2008
DOI: 10.1002/jnr.21619
|View full text |Cite
|
Sign up to set email alerts
|

Expression of polyalanine stretches induces mitochondrial dysfunction

Abstract: In recent years, several novel types of disorders have been characterized, including what have been termed polyalanine diseases, in which patients have expanded triplet repeats in specific genes, resulting in the translation of aberrantly elongated polyalanine stretches. In this study, we showed that yellow fluorescent protein (YFP)-fused elongated polyalanine stretches localized exclusively to the cytoplasm and formed aggregates. Additionally, the polyalanine stretches themselves were toxic. We sought to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…In a previous study, we detected polyalanine tracts in a mitochondrial fraction, suggesting that polyalanine tracts associate with mitochondria (Toriumi et al . 2008).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In a previous study, we detected polyalanine tracts in a mitochondrial fraction, suggesting that polyalanine tracts associate with mitochondria (Toriumi et al . 2008).…”
Section: Resultsmentioning
confidence: 65%
“…In a previous study (Toriumi et al . 2008), we examined the effect of expanded polyalanine tracts fused with yellow fluorescent protein (YFP) on cultured cell lines.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Collectively, these data suggest that the onset of polyglutamine and polyalanine diseases may relate to the oligomerization status of the disease‐causing protein and that oligomerization itself is facilitated by the homopolymeric sequences. We previously found that polyalanine tracts were associated with mitochondria (Toriumi et al, 2008). Chaperone proteins such as Hsp40 and Hsp70 were also colocalized with aggregates formed by mutant PABPN1 having polyalanine expansion (Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…However, mitochondrial dysfunction, the formation of the mitochondrial permeability transition pore, Cyt. c release, and the translocation of pro-apoptotic BAX to mitochondria have been observed in mammalian polyA models (Toriumi et al, 2008, 2009; Bhattacharjee et al, 2012). Therefore, it might be a fruitful approach to dissect the role of mitochondria in polyA-triggered cytotoxicity in yeast.…”
Section: Neurotoxic Yeast Modelsmentioning
confidence: 98%